THE MULTIPLIER EFFECT OF BALINESE LABOR WORKING ON CRUISE SHIP - I Made Darma Oka (Institut Pariwisata dan Bisnis Internasional, 2016)
As one of the most popular destinations for international tourists, Bali has attracted a sizeable and growing labor force in the tourism sector of the economy. This fact has triggered Balinese labor force to participate in such a service industry. As a supplier of tourism labor force Bali has been increasingly successful in promoting the number of workers to be employed in cruise tourism industry. The participation rate of Balinese labor in cruise tourism industry over the last years has dramatically increased. The growth of Balinese labor who works on cruise ships in the past four years reached more than 18 percent. It is happening because they have been prepared themselves in accordance to the competencies and qualifications needed in cruise tourism industry. The Balinese labor’s participation in cruise tourism industry employment has brought major implications for their life and culture. The present study aimed to analyze the multiplier effect of Balinese labor works in cruise tourism industry overview from economic and socio-cultural perspective. The research subjects were Balinese labor who used to or were still working in the cruise tourism industry. This research used qualitative data. The collected data started from one Balinese labor having experience in the cruise tourism industry and then spread to the other workers. To answer the research questions, data collection was conducted through observation and deep interviews. The data were analyzed by qualitative analysis. In analyzing the data of economic and socio-cultural perspective of Balinese labor who work in the cruise tourism industry in the environment of life, it was done through the processing and interpretation of the data which is a series of periodic review, grouping, systematization, interpretation and reification of data so that a phenomenon has social academic and scientific value. The data analysis was conducted to find the hidden reasons behind the actions of the perpetrators of social action or geared towards social significance of social phenomena. The focus is to find what kind of mindset that glows behind a social phenomenon or to find the rationality that lies behind the social phenomena. The multiplier effect of Balinese labor working in cruise tourism industry was overviewed from economic and socio-cultural perspectives. The economic perspective likes: Balinese labor working on cruise ship able to improve the family economy, and employment for the community directly or indirectly in the cruise tourism industry. The socio-cultural perspective likes: by working on cruise ships able to motivate the other Balinese labor to works on cruise ships, with working on cruise ships can open the horizons and the way of thinking society, increase the personal discipline, make clean and healthy in their live, and then improve the science and technology in tourism especially at cruises, able to strengthen the unity of nation, anticipation for disintegration, and growth the awareness to conserve the cultural after seeing the variety of cultures in the word. Based on the conclusions above, the following suggestion can be made: the government should pay attention to the existence of Balinese labor, who work in cruise ships, to the protection of their rights as well as the relevant acts should be made clear, knowing that they serve as ambassadors of the nation that generate income for the country; and the government should provide support to Balinese laborers in accordance with their potential